Golden Heroes : Fifty Seasons of Footballer of the Year - Signy, Dennis and Giller, Norman (London Chameleon, 1997)
A look at the history of the Footballer of the Year award and motivation. With 200 photographs, including pictures of every winner and a foreword by Michael Parkinson.
Include Color Illustration
Introduce by Michael Parkinson
Keywords: Soccer players -- England